2019
DOI: 10.1186/s42234-019-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity regulates autoimmune diseases through the gateway reflex

Abstract: The brain, spinal cord and retina are protected from blood-borne compounds by the blood-brain barrier (BBB), blood-spinal cord barrier (BSCB) and blood-retina barrier (BRB) respectively, which create a physical interface that tightly controls molecular and cellular transport. The mechanical and functional integrity of these unique structures between blood vessels and nervous tissues is critical for maintaining organ homeostasis. To preserve the stability of these barriers, interplay between constituent barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…The pro-inflammatory cytokines IL-6 and IL-17A are known to play a crucial role in the pathogenesis of EAU [ 67 ]. These cytokines synergistically activate NF-κB and STAT3, resulting in enhanced expression of inflammatory chemokines in endothelial cells to recruit immune cells across the BBB or BRB into the central nervous system or retina, respectively [ 22 , 23 , 24 , 25 , 26 , 27 ]. Based on our previous study [ 21 ], we hypothesized that the protective effect of L-DOPA on suppressing the recruitment of immune cells into the retina could be mediated by the inhibition of NF-κB and STAT3 activity in the BRB endothelium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-inflammatory cytokines IL-6 and IL-17A are known to play a crucial role in the pathogenesis of EAU [ 67 ]. These cytokines synergistically activate NF-κB and STAT3, resulting in enhanced expression of inflammatory chemokines in endothelial cells to recruit immune cells across the BBB or BRB into the central nervous system or retina, respectively [ 22 , 23 , 24 , 25 , 26 , 27 ]. Based on our previous study [ 21 ], we hypothesized that the protective effect of L-DOPA on suppressing the recruitment of immune cells into the retina could be mediated by the inhibition of NF-κB and STAT3 activity in the BRB endothelium.…”
Section: Resultsmentioning
confidence: 99%
“…This neurogenic mechanism is termed the gateway reflex, and its molecular basis is the inflammation amplifier, a positive feedback loop between pro-inflammatory cytokines IL-6 and IL-17, and transcription factors STAT3 and NF-κB. The inflammation amplifier maintains a persistent and massive expression of a variety of chemokines, cytokines, and growth factors by non-immune cells like endothelial cells, thereby promoting recruitment of immune cells in affected tissues [ 22 , 23 , 24 , 25 , 26 , 27 ]. Importantly, the ability of the photopic light-mediated neural activity (the light gateway reflex) to suppress the inflammation amplifier in retinal endothelial cells reduced immune cell entry in the retina and the progression of experimental autoimmune uveoretinitis (EAU) [ 21 ], a murine model of autoimmune posterior uveitis/panuveitis [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it has been reported that nanocarriers modified on the surface by anti-ICAM-1 or VCAM-1 showed a higher uptake in an inflamed brain compared to non-targeted nanocarriers [ 182 , 183 , 184 , 185 ]. Other reports have proposed “the gateway theory” [ 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ]. According to these reports, there is a gateway by which pathogens or immune cells enter the CNS, and the mechanism of gateway formation is a massive chemokine-inducing “inflammation amplifier” through the co-activation of the NF-kB and STAT3 pathways [ 187 , 191 ].…”
Section: Bbb Functionmentioning
confidence: 99%
“…Neurogenically, endothelial function is modulated by the “gateway reflex,” or neural circuits regulating entry of immune cells to the CNS by modulating the vascular EC barrier. The gateway reflex phenomenon also contributes to recruitment of immune cells to other tissues ( 16 ).…”
Section: Normal Endothelial Functionmentioning
confidence: 99%